Restitusi Tindak Pidana yang Menimbulkan Kematian dalam Perspektif Keadilan dan Hak Asasi Manusia - Puspita, Putu Lia; Rato, Dominikus; Anggono, Bayu Dwi (Hang Tuah Law Journal, 2024)
Restitution has become a representative of the development of the criminal justice system in Indonesia, with its foundation relying on the eligibility of the rights of crime victims. Such a practice is said to have made the criminal justice system in Indonesia more humane, particularly in terms of human rights. The provision of restitution to victims of criminal acts resulting in death has occurred in Indonesia for the first time. This is based on the presence of severe human rights violations in these criminal acts. This research employs a normative-empirical method, which involves examining the implementation, application, or enforcement of the prevailing laws and regulations in Indonesia in specific legal events within the community. The balance between fulfilling the rights of both the perpetrators and the victims in criminal acts in Indonesia is increasingly pursued over time, one of which is through restitution. Restitution can be one of the efforts made to fulfill victims' rights, including in cases of murder or violence that causes the victim's death. But, it is challenging to determine an appropriate nominal amount for fulfilling restitution for victims. There is a need for a deeper examination and evaluation of the losses suffered by victims of criminal acts who have lost their lives and their right to life. Thus, the provision of restitution as a means of achieving justice for victims will be better fulfilled.